Genetic Algorithm Inspired Series TCSC Location For Congestion Management In Deregulated Power System - R.Ramaporselvi, Dr. G.Geetha, Dr. Mrunal Deshpande , J.ShriSaranyaa (International Journal of Advanced Science and Technology, 2020)
System security is one of the major challenging issues in the deregulated power network. Congestion management may be suggested to control the congestion of the transmission network for providing secure operation using FACTS devices. Series type of FACTS device like TCSC can be used to improve the line loadability, minimize the system losses and ensure the system security by maintaining the power flow of the transmission system within the maximum operating limit. This paper deals with a scheme for searching the optimal location of TCSC based on the performance index using a genetic algorithm. The proposed optimization algorithm is successfully verified on the test systems of 6 bus, IEEE-14 bus and IEEE-30 bus system using MATLAB software. The end results of simulation thus prove the effectiveness of the proposed optimization algorithm with the optimal location of TCSC